Serine protease dynamics revealed by NMR analysis of the thrombin-thrombomodulin complex - Riley B. Peacock (Nature Portfolio, 2021)
Abstract Serine proteases catalyze a multi-step covalent catalytic mechanism of peptide bond cleavage. It has long been assumed that serine proteases including thrombin carry-out catalysis without significant conformational rearrangement of their stable two-β-barrel structure. We present nuclear magnetic resonance (NMR) and hydrogen deuterium exchange mass spectrometry (HDX-MS) experiments on the thrombin-thrombomodulin (TM) complex. Thrombin promotes procoagulative fibrinogen cleavage when fibrinogen engages both the anion binding exosite 1 (ABE1) and the active site. It is thought that TM promotes cleavage of protein C by engaging ABE1 in a similar manner as fibrinogen. Thus, the thrombin-TM complex may represent the catalytically active, ABE1-engaged thrombin. Compared to apo- and active site inhibited-thrombin, we show that thrombin-TM has reduced μs-ms dynamics in the substrate binding (S1) pocket consistent with its known acceleration of protein C binding. Thrombin-TM has increased μs-ms dynamics in a β-strand connecting the TM binding site to the catalytic aspartate. Finally, thrombin-TM had doublet peaks indicative of dynamics that are slow on the NMR timescale in residues along the interface between the two β-barrels. Such dynamics may be responsible for facilitating the N-terminal product release and water molecule entry that are required for hydrolysis of the acyl-enzyme intermediate.